Pengaruh Konsentrasi Saccharomyces Cerevisiae Terhadap Biokonversi Pelepah Sawit Menjadi Bioetanol - Meliana Dewi; Adrianto Ahmad; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Oil palm is one of the plantation commodities that have important role in economic activity in Indonesia. With a total area of 11.30 million hectares and oil palm plantations produce more than 75 million tons of palm oil waste per year and palm oil has a calorific value of 3350 kcal/kg, oil palm has the potential to contribute alternative energy from the resulting biomass. In addition to being utilized as an environmentally friendly renewable energy source, conversion of palm oil to bioethanol also helps to reduce untapped waste. Producing bioethanol from oil palm frond can be done through fermentation process. Factors that affect the fermentation process one of them is the number of cells of microorganisms. The microorganism used in this study is Saccharomyces cerevisiae. The purpose of this study was to determine the effect of Saccharomyces cerevisiae concentration on fermentation process on bioethanol produced and determine the best time of fermentation to bioethanol conversion from oil palm frond. The conversion of oil palm frond into bioethanol includes of delignification of oil palm frond by using KOH solution obtained from empty fruit bunches ash extract, purification of oil palm frond using 3% H2O2 solution, hydrolysis of cellulose using 1% H2SO4 with 100ºC for 60 minutes, and fermentation using Saccharomyces cerevisiae with different concentration of Saccharomyces cerevisiae 4 g/L, 6 g/L, 8 g/L, and 10 g/L. The maximum sugar concentration produced by the hydrolysis process was 117.55 g/L. The best bioethanol content was obtained at 3.29% (v/v) or 25.97 g/L at Saccharomyces cerevisiae 8 g/L concentration and 96 hours fermentation time.Keywords: Bioethanol, Fermentation, Oil Palm Frond, Saccharomyces cerevisiae